A multi‐inversion multi‐echo spin and gradient echo echo planar imaging sequence with low image distortion for rapid quantitative parameter mapping and synthetic image contrasts. Issue 2 (25th March 2021) - Manhard, Mary Kate; Stockmann, Jason; Liao, Congyu; Park, Daniel; Han, Sohyun; Fair, Merlin; van den Boomen, Maaike; Polimeni, Jon; Bilgic, Berkin; Setsompop, Kawin
Abstract : Purpose: Brain imaging exams typically take 10‐20 min and involve multiple sequential acquisitions. A low‐distortion whole‐brain echo planar imaging (EPI)‐based approach was developed to efficiently encode multiple contrasts in one acquisition, allowing for calculation of quantitative parameter maps and synthetic contrast‐weighted images. Methods: Inversion prepared spin‐ and gradient‐echo EPI was developed with slice‐order shuffling across measurements for efficient acquisition with T1, T2, and T 2 ∗ weighting. A dictionary‐matching approach was used to fit the images to quantitative parameter maps, which in turn were used to create synthetic weighted images with typical clinical contrasts. Dynamic slice‐optimized multi‐coil shimming with a B0 shim array was used to reduce B0 inhomogeneity and, therefore, image distortion by >50%. Multi‐shot EPI was also implemented to minimize distortion and blurring while enabling high in‐plane resolution. A low‐rank reconstruction approach was used to mitigate errors from shot‐to‐shot phase variation. Results: The slice‐optimized shimming approach was combined with in‐plane parallel‐imaging acceleration of 4× to enable single‐shot EPI with more than eight‐fold distortion reduction. The proposed sequence efficiently obtained 40 contrasts across the whole‐brain in just over 1 min at 1.2 × 1.2 × 3 mm resolution. The multi‐shot variant of the sequence achieved higher in‐plane resolution of 1 × 1 × 4 mm with good image quality in 4 min. Derived quantitative maps showed comparable values to conventional mapping methods. Conclusion: The approach allows fast whole‐brain imaging with quantitative parameter maps and synthetic weighted contrasts. The slice‐optimized multi‐coil shimming and multi‐shot reconstruction approaches result in minimal EPI distortion, giving the sequence the potential to be used in rapid screening applications.